BUSINESS LOCATION, BUSINESS CAPITAL, AND INFRASTRUCTURE FACILITIES ON INCOME LEVELS OF STREET TRADERS AT WATER BOOM TOURISM OBJECT IN SAWAHLUNTO CITY - Aswan, Khairil; Hidayati, Habibatul; Sari, Rani Permata (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study aims to test the influence of business locations, business capital, and infrastructure on the income level of street vendors at waterboom tourist attractions in Sawahlunto City. This research uses quantitative methods. The population of this study was all street vendors at waterboom tourist attractions, as many as 100 respondents and a sample of 100 respondents, The sampling technique is a total sampling technique where the entire population is sampled. Data analysis using multiple linear regression analysis by using the SPSS version 20 application. The results showed that the business location has a positive and significant effect on the income of street vendors, business capital has a positive and significant effect on the income of street vendors and facilities have a positive and significant effect on the income of street vendors on waterboom tourist attractions in Sawahlunto City.